Mali : Technical Assistance Report-Tax Policy-Diagnostic Assessment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
This paper presents a diagnostic assessment of the tax policy of Mali. The diagnostic assessment looks at the country's main taxes and levies; it is supplemented by a second report on the mining and petroleum sector. Tax revenues represented 15.37 percent of GDP in 2013, up slightly from the 2012 level (14.87 percent). The revenue structure has scarcely changed since the last general assessment mission conducted in 2011, and the analysis performed then remains relevant now. Mali's corporate income tax and tax on industrial and commercial profits (IS-BIC) are in compliance with the West African Economic and Monetary Union harmonization directives. The IS-BIC rate is 30 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet